Multi-level mobile cache consistency schemes based on application requirements - Mahmoud Yagoub, Doha Elsharief (2012)
In mobile environment, maintaining cache consistency is challenging due to the inherited limitations of mobile environment. In particular, there is a need for supporting multiple levels of consistency (strict and weak levels) when maintaining mobile cache to enhance the performance of data access in a mobile environment. The multiple levels of cache consistency provided by the existing scheme are based on the mobile client interest, i.e. each mobile client is responsible to determine the consistency level of each of its cached data items based on its current requirements on that item. However, this is not an appropriate idea since the consistency of the cached data items should be determined based on the requirements of the application on that item. The mobile application may allow a degree of weak consistency to some cached data items and some critical cached data items have to be up to date with data in the source. To address this issue, this thesis proposes a new stateful scheme to maintain cache consistency in the mobile environment called Application Based Multi-Level Mobile Cache Consistency Scheme (ABMMCCS). ABMMCCS is considered the first scheme that provides multiple levels of cache consistency based on the application requirements and therefore is suitable to various mobile applications. The other issue addressed in this thesis, is the degradation in the efficiency of the stateful schemes when the application system is used by a large workgroup of mobile users with sharing data. Degradation appears in the extra overhead of the base server to assure the delivering of the updates to the massive number of clients and the increasing in the uplink bandwidth consumption. Towards this an Adaptive Dynamic Application Based Multi-level Mobile Cache Consistency Scheme(ADABMMCCS) is introduced. AD-ABMMCCS scheme has proven that it enhances the efficiency of the stateful scheme ABMMCCS when the mobile application is used by a large group of users with sharing data. The proposed schemes are evaluated analytically and experimentally. The results show that under all consistency levels, ABMMCCS has significantly reduced the overhead of the mobile client and the base server and achieved better utilization to the wireless network bandwidth compared to Multi-Level Cache Consistency Protocol (MCCP) scheme. Also the results reflect the high rate of saving in the uplink bandwidth achieved when applying AD-ABMMCCS.